# Equations (Mathematics Curriculum)

## What Is a Quadratic Equation?

A quadratic equation is a type of equation.

A quadratic equation is in the form: a, b and c are constants that stand in for particular numbers. x is a variable and can take any number. The highest power of x in a quadratic equation is 2. It has an x2 term.

Here is an example of a quadratic equation: A quadratic equation shows a curve when plotted on a graph. Here is the quadratic equation above plotted on a graph: ### Dictionary Definition

The Oxford English Dictionary defines a quadratic equation as "an equation of the second degree; specifically an equation of the form ax2 + bx + c = 0, where a, b, and c are constants and x is unknown."

## Where Does the Word Quadratic Come From?

The word 'quadratic' comes from the word 'quad', meaning "square" - because the x is squared.

## The Curriculum

A brief description is given for each mini-curriculum. Click the MORE button to learn more. Quadratic equations are equations where x2 is the highest power of x.

Quadratic equations show curves when plotted.

A quadratic equation is an equation in the form: Quadratic equations show a curve when they are plotted on a graph:  Solving a quadratic equation means finding the value of x that make the equation equal to 0.

There are different ways to solve quadratic equations.

In this mini-curriculum, you will learn how to solve quadratic equations.

To solve a quadratic equation, find the value of x that makes the equation equal to 0: ### Solve a Quadratic Equation Using Factoring

#### Factor the Equation

Write the equation as two brackets multiplying each other.

Here is an example of factoring a quadratic equation into two brackets multiplying each other:

x2 + 5x + 4 = 0

⇒ (x + 1)(x + 4) = 0

#### Solve the Equation

Equate each bracket to 0 to find the two values of x that solve the equation.

Here is an example of equating each bracket to solve the equation:

(x + 1)(x + 4) = 0

$$\:\:\:\:\:\:$$x + 1 = 0 ⇒ x = −1

$$\:\:\:\:\:\:$$x + 4 = 0 ⇒ x = −4

### Solve a Quadratic Equation Using Factoring Where Leading Coefficient Is Not 1

A quadratic equation where there is a number before the x2 can be solved using factoring.

Here is an example of factoring and solving a quadratic equation where the leading coefficient is not 1:

#### Factor the Equation

2x2 + 7x + 6 = 0

⇒ (x + 2)(2x + 3) = 0

#### Solve the Equation

x + 2 = 0 ⇒ x = −2

2x + 3 = 0 ⇒ x = −32

To solve a quadratic equation using the quadratic formula, compare the quadratic equation with ax2 + bx + c = 0 to find the values of a, b and c. Substitute these values into the formula: ### Solve a Quadratic Equation Using a Graph

To solve a quadratic equation using a graph, plot the quadratic equation on a graph and see where it crosses the x-axis.

Here is an example of a quadratic equation plotted on a graph. It is solved by x = 1 and x = 2: ## Difference of Squares A difference of squares is one squared quantity (a number or letter multiplied by itself) subtracted from another squared quantity.

Some quadratic equations are in the form of a difference of squares. They can be factored and solved in an easy way.

In this mini-curriculum, you will learn about the difference of squares.

### Difference of Squares

A difference of squares is square number (a number multiplied by itself) subtracted from another square number.

Here is an example of a difference of squares: One square number (22 = 2 × 2) is being subtracted from another square number (32 = 3 × 3).

### Solve a Quadratic Equation Using a Difference of Squares

To solve a quadratic equation using a difference of squares, factor and solve the quadratic equation.

#### Factor the Equation

Write the equation as two brackets multiplying each other.

Here is an example of factoring a quadratic equation into two brackets multiplying each other using a difference of squares:

x2 − 9 = 0

⇒ (x + 3)(x − 3) = 0

#### Solve the Equation

Equate each bracket to 0 to find the two values of x that solve the equation.

Here is an example of equating each bracket to solve the equation:

(x + 3)(x − 3) = 0

$$\:\:\:\:\:\:$$x + 3 = 0 ⇒ x = −3

$$\:\:\:\:\:\:$$x − 3 = 0 ⇒ x = 3

## Completing the Square Completing the square is a way of writing a quadratic equation.

In this mini-curriculum, you will learn about completing the square.

### Perfect Square Trinomials

A perfect square trinomial is the result of squaring a binomial (two terms added or subtracted together).

Here is an example of a perfect square trinomial: ### Completing the Square

Completing the square uses a perfect square trinomial to rewrite quadratic equations.

It is called completing the square because the method can be visualised as a square. ### Complete the Square

To complete the square on a quadratic equation, write it as a squared binomial plus (or minus) a number.

Here is an example of completing the square on a quadratic equation: 